Association among Soluble Tumor Necrosis Factor Receptor I, Matrix Metalloproteinase-9, Procollagen C-terminal Propeptide type I, and N-Terminal proBrain Natriuretic Peptide in Heart Failure - Mona Yolanda; Marsetio Donosepoetro; Anwar Santoso; Mansyur Arif (The Prodia Education and Research Institute (PERI), 2011)
BACKGROUND: Heart failure (HF) is associated with an increased expression of proinflammatory cytokines, especially soluble tumor necrosis factor receptor I (sTNFR I), but the underlying mechanism to the relationship between sTNFR I activation and the progression of HF is not yet fully understood. This study aims to see the association between sTNFR I, MMP-9, PICP, and NT-proBNP in the progression of HF.METHODS: This was a cross sectional study which recruited 45 subjects with HF confirmed by echocardiography and NT-proBNP. Concentration sTNFR I, MMP-9, and PICP were measured using ELISA method, whereas NT-proBNP concentration was measured using ECLIA method. Univariate linear regression analysis, path analysis and General Linear Model were used to determine which parameters played the most significant role in HF.RESULTS: Results of the univariate linear regression and path analysis showed there was a linear relationship between sTNFR I with MMP-9, with R square of 25.8% (p=0.00; r=0.508), R square sTNFRI and MMP-9 with PICP was 14.4% (p=0.038; r=0.379) and R square MMP-9 and PICP with NT-proBNP was 39.6% (p=0.00; r=0.629). From the General Linear Model we found that the important predictor for HF was through MMP-9 and PICP.CONCLUSION: sTNFR I as a proinflammatory factor is one of the factors involved in the heart failure as seen by NT-proBNP through activation of brosis (PICP) and remodeling factor (MMP-9).KEYWORDS: sTNFR I, MMP-9, PICP, NT-proBNP, heart failure